Controlling Weeds in Major Pulse Crops by integrated weed management - Kaur, Ramanjit; Kaur, Simerjeet (Indian Farming, 2018)
While cultural practices are at the backbone of an integrated weed management plan, they alone may not be enough to secure adequate weed control and chemical control measures are required for timely management. To maximize the effectiveness of any weed management practice and avoid yield reduction, it is important to target the proper crop and weed growth stage. Integrated weed management has potential to achieve higher productivity and profitability through efficient utilization of resources and better weed suppression. An integration of herbicide, mechanical/ manual and/or cultural options that could be profitable in most pulses and pulse-based cropping system through controlling weeds; however, it is crop-specific, location-specific and environment-dependent. Therefore, efficient IWM modules/ schedules should be studied across pulses, and pulses-based cropping systems for different agro-climatic regions of the country for efficient management of weeds.